Impact of board characteristics and environmental commitment on adoption of voluntary integrated reporting: evidence from India - Shinu Vig (Cogent Business & Management, 2024)
The main objective of the study is to examine the effect of board characteristics, such as board independence, board diversity (BDv) and absence of chairman-duality, and commitment to environmental disclosures on the voluntary adoption of integrated reporting (IR) in the Indian companies. India presents a unique setting for research study in terms of its voluntary framework and the accelerating adoption of IR framework by companies in India. The sample set comprised the companies listed in the Nifty 50 index of National Stock Exchange of India. The study employed a content analysis method to collect the data relating to board characteristics, environmental commitment (EC) and adoption of IR for the period 2014–2015 to 2020–2021. It was found that board independence, absence of chairman duality, EC, leverage (Lev), firm size and profitability were significantly related to the IR. BDv and firm age were not found to have any significant impact on IR by the sample companies. The study emphasizes the role of board independence (Bin) as an important determinant in explaining the reporting choices of a company. It makes a unique contribution to literature by investigating the impact of companies' EC on the adoption of IR.
Keywords: 650; Integrated reporting; board independence; board diversity; environmental commitment; voluntary reporting; stakeholder-agency theory